Unintended Delays in Pediatric Postoperative Antibiotic Administration from Overly Complex CDS Instructions - Kandaswamy, Swaminathan; Thompson, Sarah; Ray, Edwin; Ruska, Tracy; Orenstein, Evan (Applied Clinical Informatics, 2025)
The timely administration of postoperative antibiotics is crucial for preventing surgical site infections. Despite surgical ordering workflows designed to facilitate care across settings, delays in antibiotic administration posttransfer to the pediatric intensive care unit (PICU) were identified. We aimed to develop a clinical decision support (CDS) system to enhance timely order activation in a large pediatric health system. We hypothesized that the time to release signed and held orders by PICU nurses would decrease after implementation of an electronic health record alert, ultimately reducing time to antibiotic administration.This study aimed to describe the CDS design for the timely release of postoperative orders, evaluate its effectiveness, and share lessons learned from its implementation.Stakeholder interviews and a staged implementation approach were employed to develop and implement the CDS in one of the two PICUs. An interruptive alert was designed to prompt nurses to release specific signed and held orders. The study period spanned from January 2019 to August 2024, with pre- and postintervention comparisons of the mean time to release medication orders.The alert was used from May to December 2021, but was associated with increased time to release orders. Postintervention usability testing revealed confusion among nurses, leading to the alert's discontinuation. A post hoc analysis suggested that the observed delays might align with seasonal trends rather than the CDS intervention.The CDS implementation had unintended adverse effects on order release times, emphasizing the importance of monitoring and evaluating such systems postimplementation. Usability testing highlighted the complexity of the alert messaging and the importance of including end-users in the design phase. Extended evaluation periods are recommended to discern CDS impact accurately. The study also underscores the necessity of assessing whether a technological or workflow/process change is needed in response to safety reports.
Keywords: clinical decision support; pediatrics; sociotechnical aspects of information technology; implementation and deployment